Merging yoga and occupational therapy for Parkinson's disease - Swink, Laura A., author; Schmid, Arlene A., advisor; Atler, Karen E., committee member; Fruhauf, Christine A., committee member; Fling, Brett W., committee member (Colorado State University. Libraries, 2019)
Purpose: The purpose of this dissertation was to develop a fall risk self-management program for people with Parkinson's disease (Merging Yoga and Occupational Therapy for Parkinson's Disease [MY-OT for PD]), conduct a feasibility and pilot study, and analyze outcomes following the MY-OT for PD program. Method: This dissertation includes three studies. Study One was a qualitative study which focused on the adaptation of a program originally designed for individuals with chronic stroke (i.e. Merging Yoga and Occupational Therapy) and development of a new program to specifically meet the needs of people with Parkinson's disease (PwP) (i.e. MY-OT for PD). To complete Study One, we conducted a focus group with PwP and nine expert interviews. Study One results led to the creation of Stage 1 manuals to guide the MY-OT for PD program. In Study Two, we completed the 8-week (14-session) MY-OT for PD program and focused on feasibility and pilot testing. Feasibility was assessed related to the process, resources, management, and scientific basis of the program. The following outcome measures were collected: five fall management scales, concern about falling, balance, balance confidence, and self-reported falls. Study Three was a mixed-methods analysis of health-related quality of life following the MY-OT for PD program. The quantitative outcome was a HRQoL standardized assessment specifically for PwP. The qualitative data were collected via two focus groups with participants after the program in which participants were asked about eight HRQoL domains from the quantitative assessment. Results: In the qualitative development study, three themes were identified related to revision of the MY-OT program (and development of Stage 1 manuals): revisions to the guiding model, revisions to content, revisions to delivery. We outlined changes to the manuals in relation to each theme and developed a new guiding model (the PD Fall Risk Model), altered manual content, and altered delivery aspects of the manual to create the PD-specific MY-OT for PD Stage 1 program manuals. We then implemented and tested the 8-week, 14-session MY-OT for PD program. Eighteen participants enrolled, one dropped out during the control period, and 17 participants completed an average of 12.82/14 sessions. Improvements were seen on all outcome measures, and significant differences were seen between the control and intervention periods on one of the fall management scales and balance, with significantly greater scores improvements during the intervention period as compared to the control period. HRQoL results were mixed because quantitative results showed no significant differences in HRQoL following the MY-OT for PD program, while qualitative results showed noted improvements in all HRQoL domains. Conclusion: MY-OT for PD is one promising program that decreased the number of self-reported falls during the intervention, improved balance, and participants reported improvements in HRQoL. In order to complete future trials, MY-OT for PD would need to be modified based on participant feedback and analysis of outcomes following the feasibility and pilot testing in Studies Two and Three.
Keywords: fall risk; yoga; occupational therapy; community-based; self-management; Parkinson's disease